Thyroid Status in Patients with Low Serum Ferritin Level (Bangladesh Journal of Medical Biochemistry, 2013)
Iron deficiency is the most important but preventable nutritional problem in Bangladesh. Thyroid peroxidase, an iron containing enzyme, is essential for initial two steps of thyroid hormone synthesis which is a component of tissue iron. Tissue iron diminishes early in the course of iron deficiency. So thyroid hormone level may be altered in iron deficient patients. This case-control study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2006 to June 2007. This study was done to find out the changes of thyroid hormonal activity in iron deficiency.In this study 72 subjects were selected from the out-patient department of the hospital. Patients with low serum ferritin level